How is the theoretical domains framework applied to developing health behaviour interventions? A systematic search and narrative synthesis - Fiona Cowdell; Judith Dyson (BMC, 2019)
Abstract Background Enabling behaviour change in health care is a complex process. Although the use of theory to inform behaviour change interventions is advocated, there is limited information about how this might best be achieved. There are multiple models of behaviour change, however, due to their complexity they can be inaccessible to both researchers and healthcare practitioners. To support health care practitioner behaviour change, this was addressed by the development of the Theoretical Domains Framework (TDF) in 2005. Citations of the TDF and associated papers have increased exponentially. Although not predicted or intended by the authors, the TDF has also been used to investigate health behaviour change interventions. Therefore our aim was to narratively synthesize empirical evidence on how the TDF and subsequent iterations have been applied in health behaviour change to inform future intervention development. Methods Systematic search of four online databases, combined with searches for citations of key papers and key author searches, resulted in 3551 articles eligible for screening. Of these 10 met the pre-determined inclusion criteria. Screening of full-texts, data extraction and quality appraisal were independently performed by both authors. Disagreements regarding eligibility were resolved through discussion. Results Of the 10 included studies three used the TDF and seven used subsequent iterations, the Capability, Opportunity, Motivation to Behaviour / Behaviour Change Wheel to assess and /or categorise behavioural determinants to identify relevant behaviour change techniques. Two studies reported feasibility testing. Most interventions were targeted at diet and exercise. Eight reported an explicit and systematic process in applying the framework. Conclusion There is limited evidence of how the framework has been used to support health behaviour change interventions. In the included studies the process of using the framework is not always reported in detail or with clarity. More recent studies use a systematic and judicious process of framework application. From the limited evidence available we tentatively suggest that the steps proposed in the BCW appear to be sufficient for development of interventions that target health behaviour change interventions. Further research is needed to provide evidence in how the framework may be most effectively applied to intervention development. Protocol registration PROSPERO CRD42018086896.